2010
DOI: 10.1099/vir.0.026302-0
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Zta-activated lytic transcription of Epstein-Barr virus by Ku80

Abstract: Zta, encoded by the BZLF1 gene of Epstein-Barr virus (EBV), is a transcription factor that is expressed during the immediate-early stage of the lytic cycle. The expression of Zta is crucial to viral lytic development. Earlier studies showed that Ku80 is a binding partner of Zta in ZKO-293 cells and is co-purified with Zta. This study verifies the interaction between Ku80 and Zta by using glutathione S-transferase-pull-down and co-immunoprecipitation assays, and also by indirect immunofluorescence analysis. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…This positive feedback loop appears to be required for full promoter activation of BZLF1 . In addition, BZLF1 reportedly interacts with co‐activators, such as CREB‐binding protein , Ku80 and transducer of regulated CREB , to enhance activation of BZLF1‐dependent promoters.…”
Section: Transcription Factors That Mediate Bzlf1 Inductionmentioning
confidence: 98%
“…This positive feedback loop appears to be required for full promoter activation of BZLF1 . In addition, BZLF1 reportedly interacts with co‐activators, such as CREB‐binding protein , Ku80 and transducer of regulated CREB , to enhance activation of BZLF1‐dependent promoters.…”
Section: Transcription Factors That Mediate Bzlf1 Inductionmentioning
confidence: 98%
“…BZLF1 has been reported to bind to Ku80 through its C-terminal region. 23 This interaction may also prevent the Ku70/Ku80 proteins from binding to DNA DSB ends to serve as a scaffold for subsequent NHEJ repair reactions. Further work will be required to dissect the potential relationships among 53BP1, Ku80 and BZLF1 during NHEJ-mediated repair.…”
Section: Discussionmentioning
confidence: 99%
“…The DNA damage repair protein, Ku80, physically interacts with BZLF1. 23 The BZLF1 also binds to and activates p53 (refs. 24 and 25) in certain cell types, which suggests that BZLF1 has a role in inducing DNA damage.…”
mentioning
confidence: 99%
“…In the lytic stage, EBV is known to induce DNA damage and to inhibit DNA repair leading to instability of the host genome [22,23]. One EBV component that has been associated with inhibition of NHEJ function in DSB repair is the transcription factor Zta, which is encoded by the BZLF1 gene and is crucial for lytic development of EBV [24]. Co-immunoprecipitation experiments have shown that the interaction of Ku80 with Zta can be mapped to the region associated with DNA binding and dimerization, between amino acids 168 and 245 of Zta.…”
Section: Epstein Barr Virusmentioning
confidence: 99%